The immune pathogenesis of type 1 diabetes - Wong, F. Susan (Henry Stewart Talks, 2021)
The immune pathogenesis of type 1 diabetes, Genetic associations with type 1 diabetes, The role of cytotoxic CD8 T cells, The role of helper CD4 T cells, and the regulatory subset of CD4 T cells, Autoantibodies and autoreactive B cells, Environmental influences, Implications for immune-based therapy?